Evolution of computer-assisted planning systems used in implant dentistry in the first decades of the 21st century - Łomżyński, Łukasz; Mierzwińska-Nastalska, Elżbieta (Journal of Stomatology, 2017)
Digital techniques in dentistry have been developing rapidly in the past 15 years, irreversibly changing modern dentistry with the implant dental procedures, to become one of the most influenced areas of dental sciences. 3-D implant planning software systems available since the beginning of the 21st century have been evolving towards more user-friendly interfaces and more advanced planning. These new solutions make it possible to integrate the planning systems with 3-D printing devices. Authors of the following paper describe the most important advancements in the planning systems that allow the merger of 3-D CT imaging with the soft tissue visualizations acquired with the intra-oral or lab scanners, thus limiting indications for the classic double CT scanning techniques with the use of individual radiographic guides. The possibility of surgical template production independent of the software provider itself has also been described. It may significantly cut the costs of its production, but might at the same time increase the risk of potential inaccuracies due to the limitations of the available 3-D printing devices.